2018
DOI: 10.1167/iovs.18-24881
|View full text |Cite
|
Sign up to set email alerts
|

Rose Bengal and Green Light Versus Riboflavin–UVA Cross-Linking: Corneal Wound Repair Response

Abstract: PURPOSE. To study corneal wound healing after two cross-linking techniques using either rose bengal and green light (RGX) or the conventional treatment using riboflavin and UVA radiation (UVX). METHODS. Corneas of New Zealand rabbits were monolaterally treated with UVX (21 eyes) or RGX (25 eyes). Treatments involved corneal de-epithelialization (8-mm diameter), soaking with photosensitizer (0.1% riboflavin in 20% dextran for 30 minutes for UVX; 0.1% rose bengal for 2 minutes for RGX), and light irradiation (37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 35 publications
6
15
0
Order By: Relevance
“…17 Effects of RB CXL with arg on stromal cells was limited to the region closest to the anterior surface below the Bowman membrane, similar to that found for aerobic RB CXL, and substantially less deep than produced by riboflavin CXL. 5 As previously reported, after oxygen-dependent RB CXL, cell death occurred only to the same depth as found after de-epithelialization alone (no treatment control; see Fig. 5), which is about the same depth as RB penetration into the stroma.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…17 Effects of RB CXL with arg on stromal cells was limited to the region closest to the anterior surface below the Bowman membrane, similar to that found for aerobic RB CXL, and substantially less deep than produced by riboflavin CXL. 5 As previously reported, after oxygen-dependent RB CXL, cell death occurred only to the same depth as found after de-epithelialization alone (no treatment control; see Fig. 5), which is about the same depth as RB penetration into the stroma.…”
Section: Discussionsupporting
confidence: 80%
“…5), which is about the same depth as RB penetration into the stroma. 5 After anaerobic RB CXL with arg, TUNEL-labeled cells were found at a slightly but statistically significant increased depth from the anterior surface, which correlates well with the increased penetration depth of RB in arg pretreated corneas. Further studies have to determine whether this increase has any consequences in a clinical setting, especially when compared to the results observed in riboflavin crosslinking.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In animal models, RF-CXL increased corneal stiffness as determined by air puff corneal deformation imaging with finite element modeling and by optical coherence elastography (93,94), consistent with previous studies in ex vivo-treated corneas that indicated~2-fold increase in Young's modulus (95)(96)(97)(98)(99). Responses to RF-CXL in rabbit corneas included downregulation of genes for ECM components and upregulation of glycan and proteoglycan glycosylation (100) as well as stromal cell death throughout the anterior and middle stroma (65).…”
Section: Biomechanical Stiffeningsupporting
confidence: 84%
“…In more recent studies, RB 2− phototoxicity to keratocytes in the corneal stroma has been observed and studied , which was consistent with earlier studies showing that R5P 2− photosensitization causes phototoxicity in the same tissue . The reason for greater photocytotoxicity in corneal keratocytes compared with dermal fibroblasts is not clear.…”
Section: Photosensitized Protein Crosslinking Versus Photodynamic Effectsupporting
confidence: 76%